Nonequilibrium thermodynamics : transport and rate processes in physical and biological systems - Demirel, Yasar (Elsevier, 2002)
The book begins with a brief review of equilibrium systems and transport and rate processes, then covers the following areas: theory of nonequilibrium thermodynamics; dissipation function; entropy and exergy; analysis and case studies on using the second law of thermodynamics; economic impact of the nonequilibrium thermodynamics theory; analysis of transport and rate processes; membrane transport; dissipative structures and biological systems; and other thermodynamic approaches and extended nonequilibrium thermodynamics. Summarizes new applications of thermodynamics as tools for design and optimisation Covers second law and exergy analysis for sustainable development Promotes understanding of the coupled phenomena of natural processes.